Ficha técnica no processo de desenvolvimento de produtos de vestuário: considerando o conteúdo informalidade - MONTE, Ana Laís de Oliveira (2017)
The present research is a study about the importance of the clothing tech pack in the development of products in clothing industry, considering its information content. The objective is to identify the different types of tech packs in the industries and to understand how their informational design can facilitate the productive process, avoiding errors and waste. For that, the survey was carried out in clothing industries from São Luís (MA), and the tech packs used in the production process were collected, which were organized regarding the different types found, considering the models proposed by Araújo (1999), Rigueiral (2002) and CITEVE (2005). Next, the informational contents of tech packs were analyzed based on the variables of Mijksenaar (2001), concluding with the elaboration and application of a questionnaire in order to understand how the users understand the importance of the tech pack. As result, it was evident that tech packs are still little used in the industries of São Luís – MA, mainly by the employees. The tech packs did not present a good hierarchy, creating noises that can difficult legibility and readability, the space for graphic representations is insufficient or has no description of details and information is still insufficient for users. The only positive common point among all tech packs is the use of fonts with size greater than 8 pt. Theses results are due to the lack of parameters to elaborate a good informational design for tech packs